2021
DOI: 10.1021/acsami.1c09333
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Thermocamouflage Materials in Supersonic Flowfields with Selective Energy Dissipation

Abstract: Camouflage refers to a creature’s behavior to protect itself from predators by assimilating its signature with the environment. In particular, thermal camouflage materials in the infrared (IR) wave are attracting interest for energy, military, and space applications. To date, several types of camouflage materials such as photonic crystals and metal–dielectric–metal structures have been developed. However, flexible camouflage materials still face challenging issues because of the material’s brittleness and anom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…[ 37,45 ] Hence, the structure of IR camouflage materials should be changed, such as disconnecting the brittle part to reduce the mechanical stress. [ 42 ] As a dielectric layer, silicon nitride (Si 3 N 4 ) was adopted for FAM. The transparent material, such as ZnS [ 46 ] or Al 2 O 3 , [ 47 ] is generally used for IR camouflage materials because its lattice vibration in IR band induces additional resonances.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 37,45 ] Hence, the structure of IR camouflage materials should be changed, such as disconnecting the brittle part to reduce the mechanical stress. [ 42 ] As a dielectric layer, silicon nitride (Si 3 N 4 ) was adopted for FAM. The transparent material, such as ZnS [ 46 ] or Al 2 O 3 , [ 47 ] is generally used for IR camouflage materials because its lattice vibration in IR band induces additional resonances.…”
Section: Resultsmentioning
confidence: 99%
“…[ 37 ] It implies that the flexible IR camouflage material with the dielectric layer not to induce multi‐resonances should be assembled to the flexible microwave absorber (FMWA) separately. Disconnecting the brittle layer as the engineering solution to reduce the mechanical stress leads to the flexible structure for arbitrary surfaces [ 42 ] similar to the conventional IR camouflage materials. Based on these materials, we change the function of flexible IR camouflage materials in having IR camouflage and microwave transparency, then multispectral camouflage materials can be realized by assembling each IR and microwave camouflage material.…”
Section: Introductionmentioning
confidence: 99%
“…As a countermeasure to novel detection systems, many researchers have studied various camouflage materials whose electromagnetic (EM) behaviors can be manipulated in particular spectral ranges. Because visible colors are generated by the reflection of visible light and infrared signatures are obtained from surface emissions based on temperature and emissivity, color filters with subwavelength structures have been studied extensively for controlling visible colors , as well as photonic or plasmonic resonators for controlling infrared signatures. …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, to address the EM properties in a multispectral range, several artificial materials have been studied, such as thin-film stacks, , hierarchical materials combining two or more materials working in different spectral ranges, and metal–dielectric-metal (MDM) structures having broad tunable ranges. , Based on these materials, few recent studies have reported on multispectral camouflaging (e.g., visible to microwave, visible to infrared, ,,, and infrared to microwave) with the aim of lowering signature levels by assuming a constant-intensity background. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation